2008
DOI: 10.1089/aid.2008.0062
|View full text |Cite
|
Sign up to set email alerts
|

The TRAIL of Helpless CD8+T Cells in HIV Infection

Abstract: Our understanding of how CD4 ϩ T cells can regulate CD8 ϩ T cell responses in HIV infection is still incomplete. Recent evidence obtained in mice suggests that CD4 ϩ T cell help is required for efficient CD8 ϩ T cellmediated immunity in chronic infection: CD8 ϩ T cells primed in the absence of such help release the TNF-related apoptosis-inducing ligand TRAIL and undergo apoptosis. Using a novel ELISPOT assay, in the present study we show that CD8 ϩ T cells are also a source of the antigen-specific TRAIL respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
(62 reference statements)
2
9
0
1
Order By: Relevance
“…These markers and cytokines are associated with exhaustion and/ or apoptosis. There are other markers and cytokines linked to P38 activation, which are also shown to be elevated in HIV-1 infection including TGF-b1 [49] and TRAIL [50]. Additional analysis of these immunological markers in HIV infection may further emphasize the critical role of P38 signaling in HIV infection.…”
Section: Hiv Infection and P38 Signalingmentioning
confidence: 98%
See 1 more Smart Citation
“…These markers and cytokines are associated with exhaustion and/ or apoptosis. There are other markers and cytokines linked to P38 activation, which are also shown to be elevated in HIV-1 infection including TGF-b1 [49] and TRAIL [50]. Additional analysis of these immunological markers in HIV infection may further emphasize the critical role of P38 signaling in HIV infection.…”
Section: Hiv Infection and P38 Signalingmentioning
confidence: 98%
“…They concluded that sustained ERK activation was required to produce IL-2 through T-cell receptor activation. TNF-a Inflammation [42] HIV* TGF-bl, TRAIL Exhaustion, Apoptosis [49,50] * Biomarkers that are upregulated in HIV-1 infection and play a role in the P38 pathway, but without a reported connection between HIV and P38…”
Section: Hiv Infection and Erk Signalingmentioning
confidence: 99%
“…Specifically, CD8 + T cells activated without CD4 + T cell help express TRAIL and undergo AICD upon secondary Ag stimulation (Janssen et al, 2005; Wolkers et al, 2011; Feau et al, 2012; Wolkers et al, 2012). Immune unresponsiveness associated with the generation of such TRAIL-expressing ‘helpless’ CD8 T cells has been reported in a number of experimental models and clinical settings (Hamilton et al, 2006; Griffith et al, 2007; Kuerten et al, 2008; Gurung et al, 2010; Unsinger et al, 2010; Griffith et al, 2011; Gurung et al, 2011), but this concept has proven to be more tenuous in some models of infection (see below) (Badovinac et al, 2006; Sacks & Bevan, 2008). However, apoptosis does not always result in tolerance, as it seems to be the case of lymphocyte apoptosis.…”
Section: Immunotherapy Involving Trail Receptor Agonists In Non-camentioning
confidence: 99%
“…204 It will be interesting to determine whether CD8 + T cells primarily express TRAIL within the intracellular inflammatory milieu of an HCV-infected liver and whether TRAIL blockade can restore T-cell function and reverse hepatotoxicity. 205 …”
Section: Pathogenesis Of Accelerated Liver Disease In Patients With Hmentioning
confidence: 99%